2023
DOI: 10.1037/mac0000069
|View full text |Cite
|
Sign up to set email alerts
|

What happens to memory for lecture content when students take photos of the lecture slides?

Abstract: Students often take photos of slides during lectures. Research on the photo-taking-impairment effect suggests that this behavior could impair memory for lecture content, whereas other work suggests that photo-taking could cause memory benefits, at least for visually presented information. Two experiments examined the effect of photographing lecture slides on memory for information that appeared on the lecture slides as well as information only spoken aloud by the lecturer. In Experiment 1, participants were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Indeed, photo‐taking goals could help elucidate the mixed literature examining photo‐taking effects on memory. Some studies have indicated that photo‐taking can impair memory for photographed information (Henkel, 2014; Lurie & Westerman, 2021; Soares & Storm, 2018, 2022b), while others have found the opposite effect: that photo taking benefits memory for photographed information (Barasch et al, 2017; Ditta et al, 2023). It is possible that taking photos with different goals in mind or in different situations could trigger different cognitive processes and result in different memory effects of photo taking.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, photo‐taking goals could help elucidate the mixed literature examining photo‐taking effects on memory. Some studies have indicated that photo‐taking can impair memory for photographed information (Henkel, 2014; Lurie & Westerman, 2021; Soares & Storm, 2018, 2022b), while others have found the opposite effect: that photo taking benefits memory for photographed information (Barasch et al, 2017; Ditta et al, 2023). It is possible that taking photos with different goals in mind or in different situations could trigger different cognitive processes and result in different memory effects of photo taking.…”
Section: Discussionmentioning
confidence: 99%
“…All materials are available on the Open Science Framework (Ramirez Perez et al, 2023). Two lectures about printmaking and cheesemaking were adapted from Ditta et al (2023). The lectures consisted of a slideshow with 11 slides (not including any quiz slides) for each topic and a script that was delivered live by the experimenter who screen-shared the slides during each session.…”
Section: Methodsmentioning
confidence: 99%